Rheological and thermal stability of cationic-modified diutan gum biopolymer - Norhanis Arbaaˈin,; Rasidi Roslan,; Izan Izwan Misnon,; Mohd Hasbi Ab Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cationic diutan gum (CDG) biopolymer has been developed by incorporating a quaternary amine group on diutan gum (DG) structure to improve the thermal and rheological properties. The modification was performed by mixing DG with different N-(3-chloro-2-hydroxypropyl) trimethyl ammonium chloride (CHPTAC) concentration to produce CDG in the presence of sodium hydroxide. The FTIR results confirmed the incorporation of cationic moieties onto the CDG chains. The surface morphology observed through FESEM showed that the smooth surface of DG was converted to a connective spherical reticular structure upon CHPTAC modification. The viscosity of CDG gelling fluid was increased after modification due to electrostatic chain interaction. Rheological properties showed that the plateau-like region was observed which signifying a stable gel response towards frequency. Thermal stability analysis using static thermal aging test showed the CDG was stable up to 170 °C suggesting this biopolymer can withstand the high-temperature requirements of the upstream petroleum industry.